A COMPARATIVE STUDY OF THE ROLE OF NURSES IN APPLYING DIFFERENT APPROACHES TO PATIENT EDUCATION IN MENTAL HEALTH SETTINGS - 1Saleh Ali Saleh Almehid Alyami, 2Sara Yahia Ahmed Al Heak, 3‏Hassan Ayed Mohammed Alyami, 4Ibrahim Awad Ali Almakaeel, 5Yahya Magbool Yahya Algareh, 6Fahad Awad Ali Almakaeel, (Chelonian Research Foundation, 2022)
Patient education is imperative in mental health offices, and medical caretakers are facilitators of education. This comparative study examined the viability of different educational strategies utilized by therapeutic experts. This study used an assortment of strategies, counting writing audits, interviews, and overviews, to assess the effect of these techniques on understanding and compliance with treatment. The findings indicate that there's a need for mediation within the field of brain research, utilizing numerous diverse strategies and their effects. This highlights the significance of individualized instructive intercessions to meet patients' special needs. Whereas the study's suggestions for nursing care highlight the critical role of nursing staff in persistent education, proposals for future inquiries recommend the significance of investigating more techniques to progress brain research education. Keywords: mental health, patient education, nurses, comparative study, educational approaches